2008
DOI: 10.2459/jcm.0b013e3282f20847
|View full text |Cite
|
Sign up to set email alerts
|

Guideline recommendations for heart complications in thalassemia major

Abstract: Thalassemia major is an inherited hemoglobin disorder resulting in a chronic hemolytic anemia. Transfusion therapy together with elevated gastrointestinal absorption of iron determines iron overload, which causes most of the mortality and morbidity associated with the disease. Heart complications represent the leading cause of mortality in this disease, although, because of an improvement in chelation treatment, an important and progressive increase of life expectancy mainly as a result of a reduction in morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 82 publications
1
69
0
2
Order By: Relevance
“…MRI represents the only noninvasive technique to quantify myocardial iron burden (30). In particular, iron overload in MRI is associated with an effect termed susceptibility-induced relaxation (31).…”
Section: Discussionmentioning
confidence: 99%
“…MRI represents the only noninvasive technique to quantify myocardial iron burden (30). In particular, iron overload in MRI is associated with an effect termed susceptibility-induced relaxation (31).…”
Section: Discussionmentioning
confidence: 99%
“…MRI is the only technique that quantitatively and noninvasively assesses both myocardial and liver burden (4). MRI multi-echo T2-star (T2*) sequences allow rapid monitoring of iron deposition, exploiting the fact that paramagnetic iron compounds produce variability in susceptibility, shortening the T2* relaxation time (5).…”
mentioning
confidence: 99%
“…Indeed, intravascular hemolysis has been linked to pulmonary hypertension (19,24,26,45,59), systemic vasculopathies (27,28,50,52,53,60), and cardiovascular complications (11,25,30,39). Although such studies have suggested that CF-Hb likely plays important roles in vascular disease, the actual contribution of CF-Hb to disease pathology has drawn controversy, particularly in sickle cell disease (SCD) (9,18).…”
mentioning
confidence: 99%